Fundamentals of geomorphology - Huggett, Richard J. (Milton Park, Abingdon, Oxon Routledge, 2011)
This extensively revised, restructured, and updated edition continues to present an engaging and comprehensive introduction to the subject, exploring the world's landforms from a broad systems perspective. It covers the basics of Earth surface forms and processes, while reflecting on the latest developments in the field. Fundamentals of Geomorphology begins with a consideration of the nature of geomorphology, process and form, history, and geomorphic systems, and moves on to discuss: -- -Structure: structural landforms associated with plate tectonics and those associated with volcanoes, impact craters, and folds, faults, and joints. -- -Process and form: landforms resulting from, or influenced by, the exogenic agencies of weathering, running water, flowing ice and meltwater, ground ice and frost, the wind, and the sea; landforms developed on limestone and landscape evolution, a discussion of ancient landforms, including palaeosurfaces, stagnant landscape features, and evolutionary aspects of landscape change. -- This third edition has been fully updated to include a clearer initial explanation of the nature of geomorphology, of land-surface process and form, and of land-surface change over different timescales. The text has been restructured to incorporate information on geomorphic materials and processes at suitable points in the book. Finally, historical geolomorphology has been integrated throughout the text to reflect the importance of history in all aspects of geomorphology. -- Fundamentals of Geomorphology provides a stimulating and innovative perspective on the key topics and debates within the field of geomorphology. Written in an accessible and lively manner, it includes guides to further reading, chapter summaries, and an extensive glossary of key terms. The book is also illustrated throughout with over 200 informative diagrams and attractive photographs, all in colour. --Book Jacket.
1.What is geomorphology? -- 2.Introducing process and form -- 3.Introducing history -- 4.The geomorphic system -- 5.Plate tectonics and associated structural landforms -- 6.Volcanoes, impact craters, folds, and faults -- 7.Weathering and associated landforms -- 8.Hillslopes -- 9.Fluvial landscapes -- 10.Glacial and glaciofluvial landscapes -- 11.Periglacial landscapes -- 12.Aeolian landscapes -- 13.Coastal landscapes -- 14.Karst landscapes -- 15.Landscape evolution: long-term geomorphology.
College of Science Library has electronic copy. Kindly send us message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Keywords: Geomorphology; Electronic books